2014
DOI: 10.1063/1.4875029
|View full text |Cite
|
Sign up to set email alerts
|

Damping properties for vibration suppression in electrohydraulic servo-valve torque motor using magnetic fluid

Abstract: A new adaptive resonance frequency of piezoelectric components used for vibration damping Experiments on acoustic streaming in a fluid layer between vibrating surfaces and amplitude-dependent damping of vibrations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…According to [3], p* can be expressed as (4) where p is the pressure in magnetic fluid in the absence of magnetic field, p s is magnetostrictive pressure which can be negligible for an incompressible magnetic fluid, and p m is the fluid-magnetic pressure in magnetic fluid which can be expressed as (5) According to divergence theorem, for , we have (6) where da is the infinitesimal area element, n is the unit vector normal to da pointing to magnetic fluid, S m is the surface of the magnet, and S c is the surface of the container as shown in Fig. 1.…”
Section: Theoretical Analysis Of Magnetic Levitation Forcementioning
confidence: 99%
See 1 more Smart Citation
“…According to [3], p* can be expressed as (4) where p is the pressure in magnetic fluid in the absence of magnetic field, p s is magnetostrictive pressure which can be negligible for an incompressible magnetic fluid, and p m is the fluid-magnetic pressure in magnetic fluid which can be expressed as (5) According to divergence theorem, for , we have (6) where da is the infinitesimal area element, n is the unit vector normal to da pointing to magnetic fluid, S m is the surface of the magnet, and S c is the surface of the container as shown in Fig. 1.…”
Section: Theoretical Analysis Of Magnetic Levitation Forcementioning
confidence: 99%
“…Later in the book titled "ferrohydrodynamic", Rosensweig gave a detailed description on the particular magnetic levitation force (selfsuspension buoyancy) by means of magnetic fluid stress tensor [3]. Up to now, this property of magnetic fluid has been exploited in many innovative devices, such as dampers [4][5][6], sensors [7][8][9][10][11], actuators [12][13][14], bearings [15,16], micromechanical system [17][18][19] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 A lot of work has been done to study the impact of the torque motor on EHSVs. For example, Li [10][11][12][13] analyzed the influence of magnetic fluid filled into air-gaps on the dynamic characteristics of EHSV, and concluded that the dynamic characteristics of the EHSV are improved, but the amplitude of output torque is reduced because the magnetic fluid leads to increased damping. Gordić 14 did research on the effects of the variation of torque motor parameters on servo valve operation.…”
Section: Introductionmentioning
confidence: 99%
“…When first invented in 1965 by NASA's Steven Papell, ferrofluids were used as a liquid rocket fuel that could be drawn toward a pump inlet in weightlessness environment by applying a magnetic field [4]. Up till now, ferrofluids have been successfully applied in many fields, such as sealing [5][6][7], lubrication [8,9], damping system, [10] sensors, [11] target drug delivery [12] and so on.…”
Section: Introductionmentioning
confidence: 99%